Trust, Norms, and Networks: Social Capital’s Role in Community-Based Tourism in Tambakrejo Village, Indonesia - Putri, Laura Diana; Prayitno, Gunawan; Hidayat, Ar. Rohman T.; Siankwilimba, Enock (Journal of Regional and Rural Studies, 2025)
CBT has evolved as a transformative approach to sustainable tourism development, particularly in rural and coastal areas. The principles of CBT are highly relevant, as community involvement is the key to sustainability. Therefore, the success of CBT implementation does not solely depend on the potential of tourism attractions, but also on the social capital of the community, as it involves both community participation and governance. This study explores the role of social capital in shaping the success of CBT implementation in Tambakrejo Tourism Village, Malang Regency, Indonesia. Using a quantitative approach, data were collected from 270 community members and analyzed through stepwise multiple linear regression to identify indicators influencing CBT. Based on the significance test results, five indicators had p-values < 0.05, namely trust in village government (K3), trust in outsiders (K4), obedience to government regulations (N3), willingness to cooperate in village development (J1), and willingness to express opinions during meetings (J2), indicating that each has a significant influence on community perceptions of CBT. The adjusted R-squared value was 0.55, meaning that 55% of the variation in CBT implementation can be explained by these five social capital indicators. These findings affirm that CBT cannot thrive solely on physical resources; it must also be rooted in strong social relationships and the community’s readiness for collective action.